(3GdWH GdQhMGfis - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s ((3Ydi Hf CMeO Hf eMeO GdMfai GdcGJH s)
(3ChdgG (B:s
(3bGd eMeO Hf RcQjG GdQGRi bO aUdJ gPG GdcJGH YTQjf aUdkG GdChd ai aVd GdYbd heOMg GdKGfi ai beY Gdghi hQOYg s
(3BNQgG (B:s
(3aEf TcG TGc ai gPg GdTQjYI hde jYQagG hde jJjbf UMJgG adjS dg EdG GdHMK hGdfXQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdadSaI hGdefWbs